The Relationship between Spiritual Well-Being and Death Anxiety among Muslims - Faiz Rabbani; Syeda Asma Gillani; Palwasha Nasir; Ramzan Shah Nawaz; Akbar Ali; Nimra Khan; Anoosha Nadeem (Research Journal of Psychology, 2025)
The present research determined the relationship between Spiritual well-being and death anxiety among adults who were Muslims. The participants are selected through convenience sampling with a total of 200 Muslims, aged 18-38 years. The data were collected through standardized questionnaires including the demographic information, Spiritual Well-being scale and the Death anxiety scale. Statistical analyses, including correlation, frequency distribution, regression, and descriptive analysis, were conducted using IBM SPSS 21. The finding indicated a significant relationship between spiritual well-being and death anxiety (r = -0.230, p < 0.01), suggesting that individuals with higher spiritual well-being experience lower death anxiety. Regression analysis further confirm that spirituality is a strong predictor of reduced death anxiety, with factors such as age, marital status also contributing to variation in anxiety levels. These results highlight the protective role of Spirituality in managing existential distress and death anxiety. Spiritual well-being should be integrated into clinical and Psychological interventions to support mental health among Muslim adults.